Investigating the Effect of Vitamin D Supplementation on Maternal Serum 25(OH)D Levels - Zahra Moudi; Zahra Ayati; Hossein Ansari; Seyed Mehdi Tabatabaei; Mahdieh Sheikhi (Mashhad University of Medical Sciences, 2021)
Background & aim: Although evidence confirms the importance of vitamin D supplementation in pregnancy, there is still a debate over the adequate daily doses of vitamin D intake. This study aimed to investigate the effect of 400 and 1,000 IU vitamin D/day on maternal serum 25 (OH) D levels. Methods: This quasi-experimental study was carried out on 74 healthy pregnant women between June 12 and September 22, 2019. The intervention group (n=44) received 1,000 IU vitamin D/day from 8 to 10 weeks of pregnancy for 17 weeks, while the control group (n=39) took multivitamin supplements (400 IU vitamin D/day) from 16 weeks of pregnancy for 12 weeks. Maternal serum 25 (OH) D levels were measured at 25-28 weeks of gestation. Data were analyzed in SPSS software (version 21) through the Chi-square, Student's t-test, Mann-Whitney U, and linear regression tests.  Results: There was no significant difference between the two groups at the beginning of the study in terms of 25 (OH) D concentration (P=0.23). The intake of 1,000 IU vitamin D/day had a significant (β=0.28, p <0.001), yet small effect (effect size=0.30), on increasing serum 25 (OH) D levels after controlling the confounding variables. About half of the females who took 1,000 IU vitamin D/day had a serum 25(OH) D level less than 30 ng/dl at 25-28weeks of pregnancy. Conclusion: Even after receiving 1,000 IU/day Vitamin D, vitamin D insufficiency was still prevalent during the second trimester of pregnancy. It seems that a higher dosage of vitamin D is required for pregnant women.